Case Report: Pyoderma gangrenosum misdiagnosed as diabetic foot - Zhang, Juyun; Jiang, Jicong; Wu, Meimei; Xiong, Qing (Frontiers in Endocrinology, 2025)
Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis characterized by pain and sterile ulcers. PG in diabetic patients is uncommon and often misdiagnosed as diabetic foot. This paper reports a case of a diabetic patient with a painful foot ulcer, ultimately diagnosed as PG.